2019
DOI: 10.1080/1369183x.2018.1550160
|View full text |Cite
|
Sign up to set email alerts
|

What factors explain anti-Muslim prejudice? An assessment of the effects of Muslim population size, institutional characteristics and immigration-related media claims

Abstract: What factors explain majority members' anti-Muslim prejudice? This is an increasingly important question to ask, but to date only relatively few studies have sought to provide answers from a cross-national comparative perspective. This study aims to help fill this gap. Using data from the seventh round of the European Social Survey (ESS) linked with country-level characteristics, our results indicate that (a) a larger Muslim population size, (b) more liberal immigrant integration policies and (c) greater state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 37 publications
6
41
0
1
Order By: Relevance
“…The country-level attributes include size of the immigrant population and economic conditions (Quillian 1995(Quillian , 1996Scheepers, Gijsberts, and Coenders 2002;Semyonov, Raijman, and Gorodzeisky 2006;Kuntz, Davidov, and Semyonov 2017;Meuleman, Davidov, and Billiet 2009), media coverage of immigration Schlueter, Masso, and Davidov 2018, in this issue), country integration policies (Schlueter, Meuleman, and Davidov 2013;Schlueter, Masso, andDavidov 2018, in this issue, Green et al 2018, in this issue), or major events occurring in the country like terrorist attacks (Schlueter, Masso, and Davidov 2018, in this issue). It is suggested that large or increasing immigration flows, deteriorating economic conditions, policies that are not aimed at strengthening integration of immigrants, negative media reports related to immigration, or negative events such as terrorist attacks may all result in more negative attitudes towards immigration in a country.…”
Section: Introductionmentioning
confidence: 99%
“…The country-level attributes include size of the immigrant population and economic conditions (Quillian 1995(Quillian , 1996Scheepers, Gijsberts, and Coenders 2002;Semyonov, Raijman, and Gorodzeisky 2006;Kuntz, Davidov, and Semyonov 2017;Meuleman, Davidov, and Billiet 2009), media coverage of immigration Schlueter, Masso, and Davidov 2018, in this issue), country integration policies (Schlueter, Meuleman, and Davidov 2013;Schlueter, Masso, andDavidov 2018, in this issue, Green et al 2018, in this issue), or major events occurring in the country like terrorist attacks (Schlueter, Masso, and Davidov 2018, in this issue). It is suggested that large or increasing immigration flows, deteriorating economic conditions, policies that are not aimed at strengthening integration of immigrants, negative media reports related to immigration, or negative events such as terrorist attacks may all result in more negative attitudes towards immigration in a country.…”
Section: Introductionmentioning
confidence: 99%
“…At the country level, explanations of prejudice and negative attitudes toward immigrants include size of the immigrant population and economic conditions ( Semyonov et al, 2006 ; Meuleman et al, 2009 ; Kuntz et al, 2017 ), media coverage of immigration ( Vaes et al, 2015 ; Schlueter et al, 2019 ), or country integration policies ( Schlueter et al, 2013 , 2019 ; Green et al, 2019 ). It is suggested that large or increasing immigration flows, perception of poorer economic conditions, policies that do not promote integration of immigrants, and/or negative media reports related to immigration may all result in more negative attitudes toward immigration in a country.…”
Section: Introductionmentioning
confidence: 99%
“…The ninth article, authored by Schlueter, Masso, and Davidov (2020), 'What factors explain anti-Muslim prejudice? A comparative assessment of Muslim population size, institutional characteristics and immigration-related media claims', examines potential explanations that could account for differences between countries in levels of anti-Muslim prejudice (Statham 2016).…”
Section: Introductionmentioning
confidence: 99%